Pengetahuan dan Perilaku Diet Purin dengan Kadar Asam Urat pada Masyarakat Dewasa - Nggarang, Bonavantura N.; Simon, Maria Getrida; Handi, Heribertus; Natul, Fransiska Kurniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the relationship between knowledge and behavior of purine diets and uric acid levels in adults in Ranging Hamlet, North Satarmese District. The method used is quantitative research with a cross sectional design. The research results showed that the majority of respondents' age distribution was 20-49 years, namely 48.8%, female gender was 56.1%, BMI status was normal 78.0% and knowledge about the purine diet was in the poor category 56.9%, negative behavior regarding the purine diet, it was 58.5% and most of the respondents' uric acid levels were in the high category, namely 56.9%. The results of statistical analysis show that there is a significant relationship between knowledge and behavior about the purine diet and uric acid levels in adults in Ranging Hamlet, North Satarmese District (p=0.000). The better the level of public knowledge and behavior regarding the purine diet, the more it can prevent an increase in uric acid levels in the body. Keywords: Uric acid, Purine Diet, Knowledge, Purine Diet Behavior